Gaps or links between hormonal therapy and schizophrenia? (Review) - Trifu, Simona Corina (Exp Ther Med, 2020)
Schizophrenia is considered the most severe and debilitating psychiatric disorder. During the 80's, first reports on abnormalities of the schizophrenic brain which could be objectively observed on MRI, CT scans and other imagistic techniques were published. This showed that schizophrenia is a disorder that goes beyond the functional aspect of the symptomatology. The ties between psychiatry and endocrinology are easily observed, even empirically, by any mental health practitioner, and mirrored by endocrinology specialists. Disorders related to menstruation phase of the menstrual cycle have a code in DSM-V, people expect women ‘to have mental disturbances’ during puberty, pregnancy, menopause and other periods of life known to cause a hormonal storm. Leaving aside those simple and common beliefs, any mental health specialist can observe the differences between men and women when it comes to psychopathology, and the differences between male and female patients when it comes to a severe disorder such as schizophrenia. Males present more severe symptoms; their evolution is worse and they tend to have more medico-legal issues. On the contrary, the current available treatments for schizophrenia tend to have some side effects easily observed by endocrinologists: from gynecomastia to breast asymmetry in women, hyperprolactinemia, weight gain and other metabolic disorders, the clinic shows us regularly what the science has already told us; that the impact of hormones on the developing brain, starting in utero and going on through life may hold the key to finding better treatments for debilitating disorders such as schizophrenia. This mini-review is focused on the role of estrogen in the evolution of schizophrenia and on reporting trials that showed how hormonal therapy (used mainly for breast cancer and osteoporosis) can improve the outcome of patients with schizophrenia.